THE EFFECTIVENESS OF THE APPLICATION OF TOTAL QUALITY MANAGEMENT STANDARDS IN ACHIEVING CONTINUOUS IMPROVEMENT IN EDUCATIONAL INSTITUTIONS: AN ANALYTICAL STUDY OF A NUMBER OF IRAQI UNIVERSITIES (American Journal of Business Management, Economics and Banking, 2023)
Higher education is considered the basic foundation for advancing the future of societies and achieving their ambitions and goals in various economic, political and social fields through the functions performed by its institutions. Higher education institutions in our contemporary world are not only considered a field of teaching, but their functions have expanded to become centers for research and planning for the future and preparing specialized human resources to confront... The needs of current and future social and economic development programs. The function of higher education institutions does not stop at merely preparing the human resources necessary for the comprehensive development process, but rather goes beyond raising the level of graduates’ performance and developing them to suit future development needs, in addition to contributing to providing solutions to current and future problems and facing the challenges and requirements of the times. Disseminating knowledge and expanding its horizons. To achieve the objectives of the study, the researcher used the descriptive analytical method and the questionnaire as a tool for collecting information and data, which was applied to a sample. (310) questionnaire forms were randomly distributed to faculty members, employees, and quality assurance departments. (233) questionnaires were retrieved when the questionnaires were subjected to the auditing stage. It was found that there were two questionnaires that were not suitable for entry into the statistical analysis stage, so they were excluded, and thus the size of the research sample became (231) respondents from those targeted in the research. The data will be analyzed and processed statistically using the statistical program SPSS.V22.